Impact of Social, Economic, and Healthcare Factors on the Regional Structure of Antibiotic Consumption in Primary Care in Poland (2013–2017) - Olczak-Pieńkowska, Anna; Hryniewicz, Waleria (Frontiers in Public Health, 2021)
Antibiotic resistance is one of the most important public health threats worldwide. Antimicrobial misuse and overuse are well-recognized risk factors for the resistance emergence and spread. Monitoring of antibiotic consumption (AC) is an important element in strategies to combat antibiotic resistance. As a result of AC surveillance in Poland, regional differences in AC levels were observed. This study aimed to characterize the regional AC in the period 2013–2017 in primary care in Poland and to assess the possible determinants that influence the AC at the regional level. The study analyzed relationships between AC and its factors (grouped in three different categories: demographic, economic, and related to the organization of healthcare). Data covered AC in primary care in 5 years period (2013–2017) from all 16 Polish voivodeships. The AC primary care data were sales data, expressed in defined daily doses (DDD) according to the WHO methodology. The yearly data on demographic, economic, and related healthcare factors were downloaded from the Central Statistical Office of Poland. Standard statistical parameters were used to characterize the AC. Non-standardized regression coefficients were used to estimate the quantitative dependence of variables. The strongest correlation was demonstrated with factors related to employment, female reproductive activity, mobility of the population, the number of outpatient consultations, and the number of dentists. A correlation was also found between population mobility and density. Recognized risk factors for increased AC should be a priority for interventions implementing and disseminating rational antibiotic policy.